Antimicrobial Resistance Phenotypic Profile of Isolates from Clinical Infections in Dogs - Sfaciotte, Ricardo Antonio Pilegi; Coronel, Lincoln Garcia; Snak, Alessandra; Bordin, Jéssica Tainá; Wildemann, Paula; Melo, Fernanda Daniele; Vignoto, Vanessa Kelly Capoia; Ferraz, Sandra Maria; Wosiacki, Sheila Rezler; Osaki, Sílvia Cristina (Acta Scientiae Veterinariae, 2017)
Background: Antimicrobial resistance is described as a condition in which a micro-organism is able to survive when exposed to an antimicrobial agent. The resistance rates to antimicrobials in companion animals have risen considerably. Studies of local antimicrobial susceptibility profiles are needed as well as education and warning about the use of tests for the identification and susceptibility of pathogenic bacterial strains. The aim of this study was to identify the main antimicrobial resistance in clinical samples of dogs, and to detect multidrug-resistant strains of importance to public health. Materials, Methods & Results: Bacterial pathogens of 77 dog infections were isolated and their sensitivity profile to antimicrobials was determined. One hundred bacterial isolates were identified. Of these, 61 were Gram-positive (55 Staphylococcus spp., 4 Enterococcus spp. and 2 Streptococcus spp.) and 39 Gram-negative (36 fermenters and 3 non-fermenters). Seventy-nine isolates were considered multiresistant following individual assessment of drugs, and 85 following the evaluation of classes. Only 3 were sensitive to all drugs. Four isolates were resistant to all classes and only sensitive to some antibiotics. Of the 55 samples of Staphylococcus spp., 36 (65.45%) were identified as phenotypically MRS. Two isolates of Enterococcus spp. were resistant to vancomycin (VRE). Also 66.67% (26/39) of the samples were positive for the presumptive test for ESBL. For the MRS-positive isolates detected in this study, chloramphenicol was the antimicrobial that showed superior sensitivity in 74.29% of the cases (27/36); therefore it is considered the most appropriate for treatment of this type of micro-organism. In case of aminoglycosides, when their resistance was checked in MRS isolates, all resistance percentages increased, implying a limited use of this class for such a type of multi-resistant micro-organism. Contrarily, in case of ESBL, a superior sensitivity was observed towards MRS isolates, thus making them a prime treatment choice for the infection caused by these micro-organisms. Discussion: Literature have reported a gradual increase in multidrug resistance towards antimicrobial agents in veterinary medicine over the past decades. In this study, 64% of multiresistant strains were considered of significant importance, notably MRS (36), VRE (2) and ESBL (26). The early identification of pathogens in animals has become an important step in order to minimize the transmission of antibacterial resistance. The increase in the number of multidrug-resistant bacteria in animals and humans demonstrates the need to develop and implement measures in order to monitor and control the spread of this resistance. It is possible that the increased drug resistance is linked to the constant exposure to these drugs and the subsequent selective pressure, causing the transfer of resistant genes between strains. Carbapenems and glycopeptides should be used with caution in veterinary medicine in order to prevent such processes of selection that develop resistance in micro-organisms to these two classes, which can result in cross-resistance between animals and humans and create obstacles in the treatment of patients, especially for the two drugs mentioned, since they are important for the treatment of nosocomial infections in humans. The resistance percentage towards fluoroquinolones was identified to be higher in Gram-positive isolates, particularly in MRS, which showed 75% resistance against this class (according to the CLSI, resistance to one fluoroquinolone antimicrobial agent provides resistance to other antimicrobials of this class). For ESBL isolates, the resistance was shown to be 50%. The resistance towards the fluoroquinolones and aminoglycosides class can be associated with the expression of the genes that produce ESBL.